(untitled) (Revista do Centro de Estudos Portugueses, 2011)
Este ensaio contempla as representações identitárias caboverdianas presentes nos contos da escritora Orlanda Amarílis e como tais representações se inserem em um projeto crítico da autora. Os movimentos diaspóricos das personagens transformam suas configurações identitárias, e o modo como elas são construídas revela um profundo questionamento a respeito do lugar que os cabo-verdianos e a literatura proveniente de Cabo Verde ocupam no cenário mundial. This paper contemplates the Cape Verde representations of identities present in the short stories of the writer Orlanda Amarilis, and in which ways these representations are introduced in a critical project of the author. The diasporic movements of the characters turn their identities’ configurations, and the way they are built reveals a profound questioning about the place in which the Cape Verdeans and the literature from Cape Verde occupy the world scenery.